The Fabrica of Andreas Vesalius : a worldwide descriptive census, ownership, and annotations of the 1543 and 1555 editions - Margócsy, Dániel; Somos, Mark; Joffe, Stephen N. (History of science and medicine library. Medieval and early modern philosophy and science, 2018)
The current work provides bibliographic information, a worldwide census, ownership records, and a description of the annotations in all the copies of Vesalius' Fabrica. It reconstructs the travels of the Fabrica across the globe since 1543 and its annotated readership.--